Durability of resin bonding to zirconia ceramic after contamination and the use of various cleaning methods. Issue 10 (October 2019) - Güers, Philipp; Wille, Sebastian; Strunskus, Thomas; Polonskyi, Oleksandr; Kern, Matthias
Highlights: An isopropanol-plasma-gas combination is effective for cleaning saliva from zirconia. Plasma with argon-oxygen and air atmospheres showed a comparable cleaning effect. Enzymatic cleaning agent was not able to sufficiently remove saliva from zirconia. Enzymatic cleaning agent showed indications of contaminating zirconia additionally. Abstract: Objectives: The aim of the study was to evaluate the influence of contamination and different cleaning methods on the tensile bond strength with a phosphate monomer containing luting resin to zirconia ceramic. Methods: After the contamination with saliva or silicone disclosing agent, 228 polished and airborne-particle abraded zirconia discs were ultrasonically cleaned with 99% isopropanol. In a second step, the specimens were either treated with argon-oxygen plasma, air plasma, enzymatic cleaning agent or did not undergo an additional cleaning process. Uncontaminated zirconia specimens were used as the control group. X-ray photoelectron spectroscopy (XPS) was used for chemical analysis of the bonding surfaces of specimens. Plexiglas tubes filled with composite resin were bonded to zirconia specimens with a phosphate monomer containing luting resin. Tensile bond strength (TBS) was tested after 3 days or 150 days water storage with 37, 500 thermal cycles. Results: XPS revealed a decrease of the carbon/oxygen ratio after plasma treatment and an increase after treatment with an enzymatic cleaning agent in all groups. All contaminated specimens showed high and durable TBS after cleaning with a combination of isopropanol and a non-thermal atmospheric plasma. After the cleaning with enzymatic cleaning agent the TBS was significantly reduced in all groups after 150 days thermal cycling. Significance: The combination of isopropanol and plasma cleaning was effective in removing salvia and disclosing agent contamination. Enzymatic clearing agent was not able to remove contamination effectively and had a negative impact on the TBS of non-contaminated specimens.